Creación de diseño instruccional para el desarrollo de competencias que estimulen la capacidad de innovar en líderes en una empresa privada de Lima Metropolitana - Pastor Mas, Irene (2020)
In the digital transformation career that has been taking place in the cosmetics sector we find in this company an opportunity for improvement in the implementation of digital solutions for the attention of its market, for which it was identified that an important attrib ute for the Innovation is server leadership. In this sense, this work aimed to develop the skills of active listening and collaborative work of the server leader as part of the generation of an innovation culture. For this, 36 leaders from the commercial a reas of those who had a general result were trained on the leadership style derived from the C3 Innovation Diagnostic Psychometric Test. An instructional design was made based on constructivism and the methods of process evaluation were diverse. It was inc orporated into the practical leaders associated with collaborative work and active listening during the development of their projects, as well as in team management. Consequently, the leaders of the commercial areas managed to adopt the competences of acti ve listening and collaborative work referred to the server leader as an initial part of the generation of a culture of innovation.